MEASUREMENT OF NATURAL RADIOACTIVITY IN SOME SAND AND BRICK IN VIETIANE PROVINCE, LAO PDR - Xayheungsy, Sonexay; Thanh, Nguyen Cong; Nam, Le Dai; Giang, Vu Ha; Khiem, Le Hong (IJRDO-Journal of Applied Science, 2018)
The results of the fist investigation of the activity concentration of some sand samples collected at various locations in Vientiane Capital and Thoulakhom district of Lao People’s Democratic Republic (PDR) and bricks produced by a most famous Lao Mai company are presented in this work. The activity concentration of naturally occurring radionuclides 226Ra, 232Th and 40K in the samples were determined by gamma spectrometer using a semiconductor detector HPGe. The activity concentration of naturally occurring radionuclides are in the range from 9.47±0.08 to 19.88±0.13 with the mean of 14.22± 0.30 for 226Ra, from 9.54±0.13 to 32.05±0.33 with the mean of 20.05±0.66 Bq.kg-1 for 232Th and from 229.57±2.96 to 545.40±5.65 with the mean of 447.37±13.85 Bq.kg-1 for 40K. These mean values of the activity concentration are lower than the average worldwide ones, which are 33, 45 and 420 Bq.kg-1 for 226Ra, 232Th and 40K. For the brick samples, the mean values for 226Ra, 232Th and 40K in Bq.kg-1 are 41.59±5.43, 54.79±7.62 and 614.60±34.90, respectively. The obtained activity concentrations of naturally occurring radionuclides were used for estimation of all radiation hazard indices including the absorbed gamma dose rate in air at 1m above the ground surface, the radium equivalent activity, the external hazard index and internal hazard index and the representative level index. Our results show that the measure sand and brick samples do not pose any significant source of radiation hazard from naturally occurring radionuclides 226Ra, 232Th and 40K and they are safe for use in dwelling construction.